Optimization of SiO2 crystallinity for catalytic reforming of real coal tar: Impacts of elemental loading and acid treatment - Ruihang Shang; Zhaoran Yuan; Jin Deng; Shenfu Yuan (International Journal of Coal Science & Technology)
Abstract The regulation of catalytic pyrolysis products of coal tar (CT) is a great challenge due to its complex chemical composition and inter-component interactions. Herein, Fe-Ca/H-Si catalysts were prepared and used for catalytic pyrolysis of CT for upgrading quality by acid treatment and impregnation methods, and the effect of carrier crystallinity on the distribution of CT pyrolysis products was investigated. The results showed that acid treatment disrupted the ordered crystals of silica (H-Si), creating more E’-centres defects as crystallinity decreased, and generating more sites for phenol removal reactions.The phenolic conversion of CT over H-Si increased by 12.42% at 700 °C during pyrolysis compared to SiO2. Meanwhile, the lower crystallinity of H-Si produced a larger free volume, providing sites for the anchoring of Fe and Ca. Fe facilitated the cleavage of C-C bonds and promoted the conversion of naphthalenes to aliphatic hydrocarbons. Additionally, CaO altered the electron distribution of compounds such as 2-ethyl-phenol and promoted their deoxygenation. Model compound experiments showed that the Fe-Ca/H-Si catalyst achieved 79.82% phenol conversion at 700 °C, and also promoted the one-step deep reduction of naphthalene to 1-decene. These findings indicate that the Fe-Ca/H-Si catalyst offers a promising strategy for utilization of real CT.